Effect of treatment variableson the super- fast drying method on the properties of dried high – density oil palm lumber (Elaeis guineensis) - Daslizar, Arini Madira Puteri (2017)
Wood demand in industry has been increasing each year together with the increase in population and economic development of the country. Supplies of wood always decrease because of wood insufficient resources from the forest and oil palm wood can be used to solve the problem of raw material. As using it will produce value-added products will reduce the costs of production. However, the quality of OPW is inferior to and its MC is much higher (200-500%) than the common wood (<100%) and oil palm lumber need quality improvement, also it drying has been the most problem before it can be used. A “Super-fast drying method” has been recently developed by Bakar et al. (2016).and it is unique, consisted 2-step drying (contact drying and high temperature drying) with or without holing on the material. It was reported that the method capable to dry high and low-density oil palm lumber in just 3 hours without or minimum defect. As a new method, some drying parameters in this method are still need to be optimized. From the study, it has been proved that the super- fast drying method is able to improve the some properties of properties of outer part of oil palm lumber with MOE, MOR and thickness swelling test but not for the water absorption test. Unfortunately, the methods gives negatives feedback on the durability properties against white rot fungi for the outer part of lumber as the holing presence on the surface increase the presence of oxygen that allowing the growth of fungi more easily. But as a new method the anatomical and chemical test must be implement in order to know the reason behind it is happened.